Factors contributing to increased Cases of TB among HIV/AIDS patients aged 18-45 years in Entebbe General Hospital, Wakiso District. A Descriptive Cross-sectional Study. - Barbra Wafula; Glorious Orishaba (Student's Journal of Health Research, 2022)
Background:  The purpose of the study was to determine the factors contributing to increased cases of TB among HIV/AIDS patients aged 18-45 years in Entebbe general hospital, Wakiso district. Methodology:  The study employed a descriptive cross-sectional design with a simple random technique as the sampling technique. Data was collected using a semi-structured questionnaire written in the English language from 50 respondents; later analyzed manually by use of tally sheets, entered in Microsoft excel computer program, and presented in frequency tables, and figures. Results: (80%) of the respondents who had ever heard about TB before the diagnosis of the disease, (46%) got to know that they had the disease after a month, (98%) agreed that they can be cured of TB, (50%) were smoking Tobacco and (38%) commonly fed on carbohydrates, (60%) where from town, (54%) could not recall whether they had ever had any history of contact with someone who had TB, (64%) reported that family/community members they socially neglect them, (62%) were not willing to disclose their illness to family/community members and (52%) had never got any form of assistance concerning TB medication from community members.  Conclusion :  Participants possessed personal perceptions about cure of TB infection, substance use, poor diet intake, location of respondent's home place, stigma from communities, inability to disclose the illness, inadequate support from family members, poor health-seeking behaviors, self-medication, long distances and long waiting time were the overall factors contributing to increased spread of TB infections among HIV/AIDS patient aged 18-45 years.  Recommendation:  Entebbe general hospital administration should continue to carry out community out-reaches focusing on specialized education programs that will intensively enlighten community members about the effects of discrimination and stigma towards patients and misconceptions about TB, self-medication, and timely access to medical assistance.